Characters’ Use of Flouting Maxims to Build Humor in Situational Comedy Series Fresh off the Boat Season 1 - Kartikasari, Tiya (Jurnal Bahasa, Sastra, dan Studi Amerika, 2000)
This research is conducted to identify types, strategies, and functions of flouting maxims and types of humor theory in the utterances produced by the characters in Fresh Off the Boat Season 1. The discussion is then used to analyze the relation between characters’ roles in the story and their goals, the choice of flouting maxims, and the type of humor that later resulted. This research is qualitative descriptive research that applies a pragmatic approach. The data were examined using four steps of analysis: domain analysis, taxonomy analysis, componential analysis, and cultural theme analysis. The result shows that the roles of the characters and their goals in conversation influence the choice of types and strategies of flouting maxims, which later also affected the types of humor theory. The positive functions tended to fall into the incongruity theory type of humor, while the negative functions were more likely to produce the superiority and relief theories type of humor.